Organizational commitment and its role in enhancing the performance of employees : exploratory search of the views of a sample of managers and employees of the General Company for Dairy Products - حمادي, احمد عباس (Journal of Economics and Administrative Sciences, 2016)
Expected to The organizational commitment by employees increases their loyalty towards their organization and thus contribute to enhancing their performance , therefore this study aimed to discover the relationship and the impact between the organizational commitment (emotional commitment, standard commitment, continuous commitment) and the performance of employees in the company researched, additional to know the available organizational commitment levels of employees in the company researched and its impact on the performance of employees, Research was conducted at the General Company for products in the dairy to achieve the goals of research has been developed questionnaire conation (22 ) items to collect data from the study sample totaling (80) targeted employees, heads of departments and unites, the researcher has used the descriptive analytical method using the program statistical ( SPSS ) to reach to the results, the research found: trends The staff of the General Company for Dairy Products towards organizational commitment been positive It is found that the dominant type of commitment in the company is the standard commitment , positive correlation between the dimensions of organizational commitment represented by the dimensions ( emotional commitment, standard commitment , continuous commitment) collectively and individually and the performance of employees . Addition to the results included that positive significant impact organzinal commitment represented by (emotional commitment , standard commitment, continuous commitment) collectively and individually and the performance of employees, the results confirmed that the continuous commitment was among the most-dimensional effect on the performance of employees, study yielded a number of recommendations including : Introduce the idea Organizational commitment of modern and reliable as something so as to achieve the company's goals and staff alike , intensification of conferences, seminars and training courses and workshops to enhance the organizational commitment and means to improve performance, directing the company to create an emotional commitment to the relatively high levels among employees by involving them in achieving the goals of the company and the value judgment congruence with them because of its significant role in enhancing performance , maintaining talented employees of the company through raising level of the continuous commitment they have and conducting similarly prospective studies on organizational commitment and its role in enhancing the performance of employees in the General Company for Dairy Products.